Effects of Daily Iron Supplementation on Motor Development and Brain Connectivity in Preterm Infants: A Diffusion Magnetic Resonance Study - Li, Mingyan; Ji, Chai; Xuan, Weifeng; Chen, Weijun; Lv, Ying; Liu, Tingting; You, Yuqing; Gao, Fusheng; Zheng, Quan; Shao, Jie (Frontiers in Neuroscience, 2021)
OBJECTIVES: The aim of the study is to demonstrate the characteristic of motor development and MRI changes of related brain regions in preterm infants with different iron statuses and to determine whether the daily iron supplementation can promote motor development for preterm in early infancy. METHODS: 63 preterm infants were grouped into non-anemia with higher serum ferritin (NA-HF) group and anemia with lower serum ferritin (A-LF) group according to their lowest serum Hb level in the neonatal period as well as the sFer at 3 months old. 49 participants underwent MRI scans and Infant Neurological International Battery (INFANIB) at their 3 months. At 6 months of corrected age, these infants received the assessment of Peabody Developmental Motor Scales (PDMS) after 2mg/kg/day iron supplementation. RESULTS: In total, 19 preterm infants were assigned to the NA-HF group while 44 preterm infants to A-LF groups. The serum ferritin (sFer) level of the infants in A-LF group was lower than that in NA-HF group (44.0±2.8mg/L vs. 65.1±2.8mg/L, P<0.05) and was with poorer scores of INFANIB (66.8±0.9vs.64.4±0.6, P<0.05) at 3 months old. The structural connectivity between cerebellum and ipsilateral thalamus in NA-HF group was significantly stronger than that in A-LF group (n=17, 109.76±23.8 vs. n=32, 70.4±6.6, P<0.05). The decreased brain structural connectivity was positively associated with the scores of PDMS (r=0.347, P<0.05). After 6 months routine iron supplementation, no difference of Hb, MCV, MCHC, RDW and sFer was detected between A-LF and NA-HF groups as well as the motor scores of PDMS-2 assessments. CONCLUSIONS: Iron status at early postnatal period of preterm infant is related to motor development and the enrichment of brain structural connectivity. The decrease of brain structural connectivity is related to the motor delay. After supplying 2mg/kg iron per day for 6 months, the differences of the iron status and motor ability between A-LF and NA-HF groups were eliminated.